2015
DOI: 10.1016/j.otsr.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering strategy using mesenchymal stem cell-based chitosan scafolds in growth plate surgery: A preliminary study in rabbits

Abstract: Level III. Low power comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Azarpira et al . reported that growth arrest model in which the lateral 50% of the distal femoral physis was removed and was filled with a MSC-based chitosan scaffold with a resulting trend toward less angular deformity25. The aspects of autogenous vs. allogeneic MSC transplantation into the injured physeal growth zone of extremity bones remain a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Azarpira et al . reported that growth arrest model in which the lateral 50% of the distal femoral physis was removed and was filled with a MSC-based chitosan scaffold with a resulting trend toward less angular deformity25. The aspects of autogenous vs. allogeneic MSC transplantation into the injured physeal growth zone of extremity bones remain a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Regenerative cell therapies in the fast-emerging field of tissue engineering are based on the anticipation that delivered cells rebuild the affected tissues [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Various technologies tested to introduce adequate stem cells for the construction of functioning tissues and organs, both in vitro and in vivo, have had only minimal success [ 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In most cases, in vitro-constructed non-vascularized 3D tissue-engineered complex tissues based on differentiated stem cells seemed to fade upon their implantation.…”
Section: Development Of the Concept Of Cell Therapy For Pro-regenerative Treatmentsmentioning
confidence: 99%
“…encapsulation, tissue scaffolding or as a material for degradable regeneration structures [50][51][52][53]. For these composite and polymer applications, the following requirements are posed: no toxicity for the human body, no harmful interaction with the drug, no metabolic polymer transformation products excreted beyond the body, and beneficial mechanical properties if possible, to allow the transfer of the resulting stresses to the implant before the tissue recovers [50,54,55]. In the second case, composites find a structural application, i.e.…”
Section: Polymer-ceramic Compositesmentioning
confidence: 99%